2016
DOI: 10.1039/c6ra17962b
|View full text |Cite
|
Sign up to set email alerts
|

Charge–discharge studies of all-solid-state Li/LiFePO4 cells with PEO-based composite electrolytes encompassing metal organic frameworks

Abstract: Lithium batteries with high energy density can be achieved only with a metallic-lithium anode in conjunction with solid polymer electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 38 publications
2
46
0
1
Order By: Relevance
“…As shown in Figure c, the Li/PEO‐Mg‐BTC‐MOF‐LiTFSI (75/10/15, wt %)/LiFePO 4 cell exhibited a good rate capability and capacity retention at 70 °C. Additionally, a Ni‐BTC‐MOF having open metal sites was also reported to be a good filler for a PEO‐LiTFSI electrolyte to enhance its ionic conductivity (1.4×10 −4 S cm −1 at 30 °C) and its mechanical and thermal properties …”
Section: Mofs As Solid‐state Electrolytes For Lithium‐metal Batteriesmentioning
confidence: 99%
“…As shown in Figure c, the Li/PEO‐Mg‐BTC‐MOF‐LiTFSI (75/10/15, wt %)/LiFePO 4 cell exhibited a good rate capability and capacity retention at 70 °C. Additionally, a Ni‐BTC‐MOF having open metal sites was also reported to be a good filler for a PEO‐LiTFSI electrolyte to enhance its ionic conductivity (1.4×10 −4 S cm −1 at 30 °C) and its mechanical and thermal properties …”
Section: Mofs As Solid‐state Electrolytes For Lithium‐metal Batteriesmentioning
confidence: 99%
“…Composites including UiO-66 nanoparticles in PS, 23 and in PIM-1 24 , 25 have already been reported. PEG-based solid electrolytes incorporating MOFs are known, 26 – 29 but they all incorporate lower loadings (<40%) of MOF and their membrane-forming characteristics are rarely discussed in detail. Therefore, UiO-66/PEG MMMs with high MOF content (both 70 and 80 wt% MOF) are reported here to compare with the computational study and to previously reported MMMs.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of MOFs was found to enhance the ionic conductivity, compatibility, thermal stability, mechanical properties, as well as the lithium/electrolyte interfacial properties of the composite polymer electrolytes. [136][137][138][139][140] Stephan and co-workers investigated different MOFs as fillers in a PEO and lithium bis(trifluoromethanesulfonylimide) complex. [136][137][138][139] They found that the Lewis acid groups of the added MOFs may compete with the Lewis acid lithium cations for the formation of complexes with the alkoxide of the PEO chains as well as the anions of the added metal salts, thereby lowering the ionic coupling and promoting the dissociation of metal salts, thus improving the ionic conductivity.…”
Section: Electrolytesmentioning
confidence: 99%
“…[136][137][138][139][140] Stephan and co-workers investigated different MOFs as fillers in a PEO and lithium bis(trifluoromethanesulfonylimide) complex. [136][137][138][139] They found that the Lewis acid groups of the added MOFs may compete with the Lewis acid lithium cations for the formation of complexes with the alkoxide of the PEO chains as well as the anions of the added metal salts, thereby lowering the ionic coupling and promoting the dissociation of metal salts, thus improving the ionic conductivity. Despite the promises shown by these reported works on MOF-based solid-state electrolytes, further works, such as the improvement of high-current performances and optimization in solid-state electrode/electrolyte contact, remain to be done in future for their practical application.…”
Section: Electrolytesmentioning
confidence: 99%